The Multilateral Investment Guarantee Agency’s Experience with Non-Honoring of Sovereign, Sub-Sovereign, and State-Owned Enterprise Financial Obligation Guarantees : Meso-Evaluation - Independent Evaluation Group (Washington, DC : World Bank, 2022)
The Multilateral Investment Guarantee Agency (MIGA) introduced its Non-Honoring (NH) products - the Non-Honoring of Sovereign and Sub-Sovereign Financial Obligations and the Non-Honoring of Financial Obligations by a State-Owned Enterprise - in 2009. The objective of these products was to crowd-in private insurance capacity to support investments in International Development Association and Fragile and Conflict-Affected Situation countries, and to encourage state-owned enterprises to adopt good corporate governance, environmental and social sustainability practices. These products were expected to benefit guaranteed lenders through lower cost of financing and public sector borrowers through increased and more diversified funding sources. Since their introduction, the NH products have gained a substantial share of MIGA’s overall business. This report provides the first independent evaluation of MIGA’s experience with its NH products and aims to offer feedback and lessons to inform future strategies. The report reviewed all 34 NH projects implemented by MIGA between 2009 and 2019 to assess the extent to which they met their objectives and contributed to enhancing MIGA’s development effectiveness and additionality. The report invites MIGA to address questions related to the suitability of these products for IDA and FCS countries and on the methodology for evaluating their development impact.